2004
DOI: 10.1542/peds.114.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Children Who Have Received No Vaccines: Who Are They and Where Do They Live?

Abstract: Unvaccinated children have characteristics that are distinctly different from those of undervaccinated children. Unvaccinated children are clustered geographically, increasing the risk of transmitting vaccine-preventable diseases to both unvaccinated and undervaccinated children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
269
3
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(297 citation statements)
references
References 27 publications
18
269
3
7
Order By: Relevance
“…Previous studies that examined factors associated with vaccine uptake found both positive and negative associations with education level and income 21, 22, 23, 24. In this study, we found that many reasons for unwillingness to receive vaccine were similar in higher and lower education groups; however, the qualitative responses of some participants may suggest that while those with lower education levels have specific beliefs or reasons for not wanting vaccine, those with higher education levels have non‐specific preferences not to get vaccinated.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies that examined factors associated with vaccine uptake found both positive and negative associations with education level and income 21, 22, 23, 24. In this study, we found that many reasons for unwillingness to receive vaccine were similar in higher and lower education groups; however, the qualitative responses of some participants may suggest that while those with lower education levels have specific beliefs or reasons for not wanting vaccine, those with higher education levels have non‐specific preferences not to get vaccinated.…”
Section: Discussionmentioning
confidence: 95%
“…In other studies, including a previous study in Belgium [3,6,12,14], low parental educational level was significantly associated with incomplete vaccination and maternal age has also been recognized as a factor influencing vaccination [6,8,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the birth cohort of which children were recruited for this study largely received the 2003 schedule with three monovalent doses of HBV. A number of characteristics that have been found to be related to vaccination coverage in industrial countries have been taken into consideration in this 2005 survey, such as parental education, ethnicity, age, marital and working situation, birth order of the child, medical problems, side effects of vaccination, vaccine provider and having a vaccination card [3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Although high population immunity throughout the United States (through maintaining !90% MMR vaccine coverage among children aged 19-35 months and adolescents) prevents spread from most importations (7,8), coverage varies at the local level and unvaccinated children tend to cluster geographically, increasing the risk for outbreaks (9). Thus, maintaining high measles vaccination coverage is critical to prevent large measles outbreaks in the United States, and to protect and limit spread to infants too young to be vaccinated and to persons who cannot be vaccinated because of medical contraindications.…”
mentioning
confidence: 99%